2016
DOI: 10.4038/ouslj.v10i0.7335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Modification of n-Cu<sub>2</sub>O/p-Cu<sub>x</sub>S Thin Film Heterostructures for Enhanced Liquefied Petroleum Gas Sensing Properties

Abstract: We report a novel mechanism to effectively detect LP gas based on surface modification through sulphidation followed by passivation of electrodeposited n-type cuprous oxide (Cu2O), forming a thin film n-Cu2O/p-CuxS semiconducting heterostructure. Electrochemically deposited n-type cuprous oxide (n-Cu2O) thin films on Ti substrates in acetate bath were sulphided using Na2S to fabricate n-Cu2O/p-CuxS heterostructures. Subsequent passivation of these thin film structures using (NH4)2S vapor enhanced the sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Jayathilaka et al further demonstrated that (NH 4 ) 2 S vapor treatment of electrodeposited pCu 2 O films reduces resistivity by at least four orders of magnitude, while preserving structural integrity [27] and Jayathilaka et al also reported that (NH 4 ) 2 S vapor treatment of sulphided electrode posited nCu 2 O films improved photovoltaic efficiency from 0.11% to 0.54% [28]. Similar surface treated electrodeposited nCu 2 O thin films have also shown improved LP gas sensing ability in our previous work [29]. Here it was observed that both an optimal treatment of the films with (NH 4 ) 2 S vapor as well as having a minimum Cu 2 O thin film thickness was crit ical in introducing optimal response at a relatively lower oper ating temperature (~45 °C) in the presence of LP gas, while being able to recover response to ambient level in the absence of LP gas.…”
Section: Introductionsupporting
confidence: 70%
“…Jayathilaka et al further demonstrated that (NH 4 ) 2 S vapor treatment of electrodeposited pCu 2 O films reduces resistivity by at least four orders of magnitude, while preserving structural integrity [27] and Jayathilaka et al also reported that (NH 4 ) 2 S vapor treatment of sulphided electrode posited nCu 2 O films improved photovoltaic efficiency from 0.11% to 0.54% [28]. Similar surface treated electrodeposited nCu 2 O thin films have also shown improved LP gas sensing ability in our previous work [29]. Here it was observed that both an optimal treatment of the films with (NH 4 ) 2 S vapor as well as having a minimum Cu 2 O thin film thickness was crit ical in introducing optimal response at a relatively lower oper ating temperature (~45 °C) in the presence of LP gas, while being able to recover response to ambient level in the absence of LP gas.…”
Section: Introductionsupporting
confidence: 70%